POTENTIAL OF PSEUDOMONAS STUTZERI STRAINS ISOLATED FROM RHIZOSPHERIC SOIL ENDOWED WITH ANTIFUNGAL ACTIVITIES AGAINST PHYTOPATHOGENIC FUNGUS STEMPHYLIUM BOTRYOSUM - Mokrani, Slimane; Bejaoui , Bilel; Belabid , Lakhder; Nabti, Elhafid (Asian Journal of Agriculture, 2019)
Abstract. Mokrani S, Bejaoui B, Belabid L, Nabti E, Mokrani S. 2020. Potential of Pseudomonas stutzeri strains isolated from rhizospheric soil endowed with antifungal activities against phytopathogenic fungus Stemphylium botryosum. Biodiversitas 21: 47-54. In this present study, two Pseudomonas strains P4 and P5 isolated from rhizospheric soil were characterized for PGP (Plant Growth Promoting) traits production like HCN (Hydrogen Cyanid), siderophores and IAA (Indole Acetic Acid). Phylogenic tree based on 16S DNAr identification-related the two strains P4 and P5 to Pseudomonas stutzeri NR 116489 and NR 113652.1. One phytopathogenic fungus St-bt (Stemphylium botryosum) was isolated from Phaseolus vulgaris L. Macroscopic and microscopic identification attributed it to the genus Stemphylium. Antifungal activities of the two Pseudomonas strains P4 and P5 against fungus isolate St-bt had revealed very highly significant inhibition percentages of 38.46± 3.85% and 56.56± 2.22% for each strain, respectively.